EVALUASI PELAKSANAAN PROGRAM BANTUAN OPERASIONAL SEKOLAH (BOS) PADA SEKOLAH MENENGAH ATAS (SMA) DI KECAMATAN PARIGI KABUPATEN PARIGI MOUTONG - Masita, Masita (Katalogis, 2015)
This reseach aims to describe the process of School Operational Grant Program Implementation at Senior High School of Parigi Moutong Regency. The method employed is desciptive qualitative research with technique of data cellection covering observation, interview, and documentation. The research result indicates that the implementation of school operation grand program implementation at senior high school of parigi moutong regency with model not optimal yet. There are some factors influencing such as : 1). The high school of parigi moutong regency from aspect of budget operation and secccesfulness is not efficient, 2). The implemtation of school operational grand program implementaion at senior high school of parigi moutong regency from aspect of budget operation and successfulness is effective.